Telemedicine devices in internal medicine and neurology - Domeracki, Mateusz; Prylińska, Monika (Journal of Education, Health and Sport, 2019)
Introduction Monitoring of patients systems remotely with feedback send to physician and patient could be applied in many fields of medicine. Telemedicine could presumably lead to improvement of patients care and treatment both in chronic conditions and in emergency, lowering demands on costs and time resources. Material and methods Articles in the EBSCO database have been analyzed using keywords: Telemedicine devices, telemedicine devices, neurology, cardiology. The available literature is subjectively selected. Then, the newest version of every paper was searched for. Results The most important and popular types of devices used in telemedicine in internal medicine and neurology were presented. Conclusions The development of devices in telemedicine results in an increase in effectiveness in the diagnosis and treatment of patients. In addition, remote access to the results of measurements made by these devices affects the quality of treatment.